Consensus decision-making as a research method for generative justice: empirical practices from a money-less economy in Chiapas, Mexico - Araujo, Erin (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
This article examines how consensus decision-making can be used as a method in creating spaces for generative justice. Based on empirical research in a moneyless economy in San Cristobal de las Casas, Chiapas, Mexico, the project called El Cambalache has created its own exchange value where everything in the economy shares equal value. The article is a praxiography of consensus decision-making as research method.